The Role of Connexin in Ophthalmic Neovascularization and the Interaction between Connexin and Proangiogenic Factors - Chuyang Xu; Hong Zhang; Wei Zhong; Hongyan Zhou (Journal of Ophthalmology)
The formation of new blood vessels is an important physiological process that occurs during development. When the body is injured, new blood vessel formation helps the body recuperate by supplying more oxygen and nutrients. However, this mechanism can have a negative effect. In ophthalmologic diseases, such as corneal new blood vessels, neonatal vascular glaucoma, and diabetes retinopathy, the formation of new blood vessels has become a critical component in patient survival. Connexin is a protein that regulates the cellular and molecular material carried by cells. It has been demonstrated that it is widely expressed in vascular endothelial cells, where it forms a slit connection between adjacent cells to promote cell-cell communication via hemichannels, as well as substance exchange into intracellular environments. Numerous studies have demonstrated that connexin in vascular endothelial cells plays an important role in angiogenesis and vascular leakage. The purpose of this study was to investigate the effect between the angiogenesis-associated factor and the connexin. It also reveals the effect of connexin on ophthalmic neovascularization.